Six ways to get a grip on a mentorship program for residents and faculty - Harper, Lea; Hergott, Christopher A; Coderre, Sylvain; Kelly-Turner, Kenna; Davis, Melinda; McLaughlin, Kevin (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2025)
Mentorship is recognized as beneficial to the personal and professional development of physicians. It has been shown to positively influence career success and research productivity for the mentee, while being associated with increased job satisfaction and lower risk of burnout for the mentor. At an institutional level, when aligned with strategic priorities, mentorship can facilitate gender and racial equality, and improve faculty retention. Consequently, there are calls to prioritize and formalize mentorship, yet the optimal way to achieve this remains elusive. How exactly do we create a mentorship program that is viewed as effective from the perspective of the mentor, mentee, and the institution? In this article we approach mentorship as a complex system, and through this lens we aim to provide medical educators and leaders with guidance on how to create and evaluate a program that provides mentees with distributed and precision mentoring, while also aligning with institutional priorities.